Whole-body vibration decreases the proliferativeb response of TCD4+ cells in elderly individuals with knee osteoarthritis - Tossige-Gomes,R. (2012)
The aim of this study was to investigate the effect of adding whole-body vibration (WBV; frequency = 35 to 40 Hz; amplitude = 4 mm) to squat training on the T-cell proliferative response of elderly patients with osteoarthritis (OA) of the knee. This study was a randomized controlled trial in which the selected variables were assessed before and after 12 weeks of training. Twenty-six subjects (72 ± 5 years of age) were divided into three groups: 1) squat training with WBV (WBV, N = 8); 2) squat training without WBV (N = 10), and 3) a control group (N = 8). Women who were ≥60 years of age and had been diagnosed with OA in at least one knee were eligible. The intervention consisted of 12 uninterrupted weeks of squatting exercise training performed 3 times/week. Peripheral blood mononuclear cells were obtained from peripheral blood collected before and after training. The proliferation of TCD4+ and TCD8+ cells was evaluated by flow cytometry measuring the carboxyfluorescein succinimidyl ester fluorescence decay before and after the intervention (∆). The proliferative response of TCD4+ cells (P = 0.02, effect size = 1.0) showed a significant decrease (23%) in the WBV group compared to the control group, while there was no difference between groups regarding the proliferative response of TCD8+ cells (P = 0.12, effect size = 2.23). The data suggest that the addition of WBV to squat exercise training might modulate T-cell-mediated immunity, minimizing or slowing disease progression in elderly patients with OA of the knee.